Effect of Lifestyle Educational Intervention on Blood Pressure in Diabetic Patients with Hypertension - Soraya Soheili; Yaghoub Pirdehghan; Seyede Roghayeh Hosseini (Journal of Education and Community Health)
Aims: Hypertension is one of the most common and important problems of people with diabetes that its increase causes cardiovascular complications and mortality in these people. The aim of this study was to determine the effect of lifestyle educational intervention on blood pressure in diabetic patients with hypertension. Materials & Methods: In this experimental study, 74 patients with diabetes and hypertension referred to Urmia Diabetes Association in 2017 were selected by simple random sampling method and randomly divided into experimental (37 patients) and control (37 patients) groups. Educational intervention of lifestyle change was done for intervention group by providing educational pamphlets and holding educational classes in 4 sessions during 2 weeks. Data were analyzed by SPSS 16 software using chi-square test, paired t-test and independent t-test. Findings: Before intervention, the mean of systolic and diastolic blood pressure had no significant difference between two groups (p>0.05), but after intervention the mean of systolic and diastolic blood pressure in intervention group decreased significantly (p<0.001). Conclusion: Lifestyle educational intervention can significantly modulate hypertension in diabetic patients with hypertension.